Point of Sales System in InHome Café Website using Agile Methodology - Irma Amelia Dewi; Yusup Miftahuddin; Muhammad Assidiq Fattah; Cikal Bingah Palenda; Syahrul Fathurrahman Erawan (Faculty of Smart Technology and Engineering, Universitas Kristen Maranatha, Bandung, Indonesia, 2021)
The Point of Sales (POS) system is a system that supports sales transactions where POS is currently evolving because it can record sales, record inventory, print invoices, calculate profits and improve services for businesspeople and entrepreneurs. InHome Café is one of the growing cafe in Subang, Bandung. Ease of access to purchase products through online services led to an increase in transactions. At InHome Café Subang, data management, data processing, and sales transaction processing used to rely on a manual system or paper-based recording, which open to risks in data management and security. Therefore, to solve the problem, a website-based Point of Sales System was developed to record sales, collect inventory, print invoices, calculate profits using the PHP programming language with the CodeIgniter framework, and MySQL. The system was developed using the Agile development system with a reasoning that a short-term system development that emphasizes client satisfaction was required. The system functionality testing resulted in a success rate of 96.15%. Keywords: agile, café, point of sales, scrum, website